An investigation of managerial methods for minimizing wastage of food in the Indian hospitality sector (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Recently, food waste has increased significantly. According to figures provided by the FAO (Food and Agriculture Organization), 1.3 billion tons of food are exhausted annually on a global scale. We developed a technique to manage the food in practical ways in hopes of reducing food wastage. So, with the aid of an Android application, we can decrease food waste. Anyone who has a significant volume of food waste can publish a message or make a request. Also, the nearby food donors will receive your registered phone number along with details on the food that is now accessible to the community. The incredible economic expansion of India's hospitality industry has also contributed to a rise in the number of hotels throughout the nation. With the help of a field questionnaire survey, the current study aimed to inform researchers and restaurant owners about foodstuff proper waste administration in the Indian hospitality industry. It did this by compiling available data and gathering reports from professional restaurant servers